Underlying heart diseases and acute COVID-19 outcomes - Núñez-Gil, Iván J.; Fernández-Ortiz, Antonio; Eid, Charbel Maroud; Huang, Jia; Romero, Rodolfo; Becerra-Muñoz, Victor Manuel; Uribarri, Aitor; Feltes, Gisela; Trabatoni, Daniela; Fernandez-Rozas, Inmaculada; Viana-Llamas, Maria C.; Pepe, Martino; et al. (Cardiology journal, 2021)
Background: The presence of any underlying heart condition could influence outcomes during the coronavirus disease 2019 (COVID-19). - Methods: The registry HOPE-COVID-19 (Health Outcome Predictive Evaluation for COVID-19, NCT04334291) is an international ambispective study, enrolling COVID-19 patients discharged from hospital, dead or alive. - Results: HOPE enrolled 2798 patients from 35 centers in 7 countries. Median age was 67 years (IQR: 53.0-78.0), and most were male (59.5%). A relevant heart disease was present in 682 (24%) cases. These were older, more frequently male, with higher overall burden of cardiovascular risk factors (hypertension, dyslipidemia, diabetes mellitus, smoking habit, obesity) and other comorbidities such renal failure, lung, cerebrovascular disease and oncologic antecedents (p < 0.01, for all). The heart cohort received more corticoids (28.9% vs. 20.4%, p < 0.001), antibiotics, but less hydroxychloroquine, antivirals or tocilizumab. Considering the epidemiologic profile, a previous heart condition was independently related with shortterm mortality in the Cox multivariate analysis (1.62; 95% CI 1.29-2.03; p < 0.001). Moreover, heart patients needed more respiratory, circulatory support, and presented more in-hospital events, such heart failure, renal failure, respiratory insufficiency, sepsis, systemic infammatory response syndrome and clinically relevant bleedings (all, p < 0.001), and mortality (39.7% vs. 15.5%; p < 0.001). Conclusions: An underlying heart disease is an adverse prognostic factor for patients suffering COVID-19. Its presence could be related with different clinical drug management and would benefit from maintaining treatment with angiotensin converting enzyme inhibitors or angiotensin receptor blockers during in-hospital stay.